Self-Regulated Learning as Mediator on the Determinants of Mathematics Achievement in Junior High School Students in the City of DKI Jakarta Pusat - Evi Syafrida Nasution; Asmadi Alsa; Erdina Indrawati (Journal Research of Social Science, Economics, and Management, 2022)
The purpose of this study was to determine the effect of parental support, attitudes towards mathematics, and mastery goal orientation on mathematics learning achievement with self-regulated learning as a mediator. The research method that the researcher uses is a structural model with a total of 327 respondents who were taken using cluster random sampling technique. The data analysis technique used in this research is SEM AMOS. Based on the results of the model test, it is known that the influence of parental support, attitudes towards mathematics, and the orientation of mastery goals on mathematics learning achievement with self-regulated learning as a mediator, according to empirical data. Based on the results of statistical tests, it is known that parental support, attitudes towards mathematics lessons, and orientation of mastery goals have no effect on learning achievement in mathematics with self-regulated learning as a mediator